Implementation of the Flipped Classroom Learning Model Assisted by Educational Videos on Elasticity in Training Critical Thinking Skills of High School Students - T. Susi Juliani; Zuhdi Ma,ruf; Muhammad Sahal (Global READ Center, 2025)
For educational purposes, a suitable learning model is needed to support student learning activities, which in this case will be used as a learning model in the form of a flipped classroom assisted by digital-based learning videos. The purpose of this study is to describe students' critical thinking skills after using the Flipped Classroom learning model with the assistance of learning videos on the subject of elasticity. This study uses a quasi-experimental design with a posttest-only design. Based on the post-test results related to students' critical thinking skills in the experimental class, the average score was 82.40 with a standard deviation of 15.9, indicating a very critical category when viewed from the category of critical thinking skill score scale. Meanwhile, the post-test results conducted in the control class yielded an average score of 62.34 with a standard deviation of 14.2, indicating a less critical category. Thus, it can be concluded that the implementation of the flipped classroom learning model with the assistance of educational videos on the topic of elasticity was successful in developing critical thinking skills in students.